Religious Interest and Faith - Dubnikas, Kęstutis (Problemos, 2003)
The article is devoted to the analysis of the ontological justification of religion. Existential phenomenology serves as a basis to claim about the religious dimension in the common human experience which is limit relationship to the world. This limit experience becomes an issue of ultimate concern as existential significance, or, in other words, as an expression of religious interest. Faith is analysed as an immediate acceptance of existence by participating in the reality. However, the world in a limit faith does not lend itself to cognition and is not complete, but rather is perceived in a process as not-yet-being. Following Tracy's analysis of limit experience, the article investigates the issue of the meaning of religious language as well as the correlation of secularity and religion.
Keywords: religious interest; ultimate concern; limit experience and language; Nothing